Drivers of trust in relational service exchange: Understanding the importance of cross-cultural differences - Jan H. Schumann (2018)
Customer trust is of vital importance for relationship marketing in services. Service providers increasingly market their services globally, yet few researchers have addressed differences in customer trust across cultures. Our research fills this void by proposing a model, based on existing trust literature, that suggests the overall feeling of trust in the service provider depends on customers' beliefs about service providers' ability, benevolence, predictability, and integrity. The model, tested in a banking context with data from 2,284 customers in 11 countries, explains trust well across culturally diverse countries. The results of a hierarchical linear model, however, show that customers differ in the way they build trust in their service provider across cultures. Moderating effects of the cultural values of the target group largely explain this variation. Only the effect of ability on trust is robust across countries. Global service firms should consider all four trust drivers when striving to build trust. The emphasis they put on each of these trust drivers, however, should differ across countries. When applying these principles to the design of marketing activities or market segmentation, marketing managers should collect data on the cultural values of their specific target groups in particular countries or cultural milieus. © The Author(s) 2010.